Moving From Feasible Solutions to Sustainable Systems in The Built Environment - Berawi, Mohammed Ali; Sari, Mustika; Miraj, Perdana (UI Scholars Hub, 2025)
The built environment plays a crucial role in global sustainability efforts. Buildings, infrastructure, and cities consume large amounts of energy and materials that shape social behavior, and lock in environmental impacts. Over the past two decades, research has produced a wide range of technical solutions to reduce these impacts. Renewable energy systems, energy-efficient buildings, alternative construction materials, and new construction methods are no longer experimental concepts. Many have proven technical and economic potential. Yet, real-world transformation remains slow and uneven. This gap suggests that sustainability challenges in the built environment are no longer driven by a lack of technology. Instead, they are shaped by how technologies are adopted, governed, financed, and embedded within existing systems. The papers in this issue tried to understand this challenge from different scales and contexts. Together, they show that sustainability is best understood as a socio-technical transition, where technical solutions must align with institutions, markets, spatial structures, and human practices.